2020
DOI: 10.1186/s12876-020-1183-x
|View full text |Cite
|
Sign up to set email alerts
|

Faecal calprotectin is the biomarker that best distinguishes remission from different degrees of endoscopic activity in Crohn’s disease

Abstract: Background: Effective control of the inflammatory process in Crohn's disease (CD) is reflected in intestinal mucosal healing. The performances of faecal calprotectin (fcal), clinical and serologic parameters in the inflammatory activity evaluation and their correlation to the simple endoscopic score (SES-CD) are the goals of this study. Methods: Patients with CD referred for ileocolonoscopy were prospectively included and distributed according to the degree of endoscopic inflammatory activity into remission, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…Other non-invasive diagnostic tests for IBD, such as fecal calprotectin, continue to have significant differences between the reports on the sensitivity and specificity for classifying IBD patients from non-IBD [88, 89]. While high performance levels have been reported, one recent study identified a 78% accuracy for identifying patients with IBD using fecal calprotectin [90], which is approximately 10% lower than our best model. Furthermore, while we focused solely on IBD classification, ML models using microbiome composition have wider applicability than singular biomarkers such as calprotectin.…”
Section: Discussionmentioning
confidence: 59%
“…Other non-invasive diagnostic tests for IBD, such as fecal calprotectin, continue to have significant differences between the reports on the sensitivity and specificity for classifying IBD patients from non-IBD [88, 89]. While high performance levels have been reported, one recent study identified a 78% accuracy for identifying patients with IBD using fecal calprotectin [90], which is approximately 10% lower than our best model. Furthermore, while we focused solely on IBD classification, ML models using microbiome composition have wider applicability than singular biomarkers such as calprotectin.…”
Section: Discussionmentioning
confidence: 59%
“…Another limitation may be represented by the lack of colonoscopy to assess endoscopic remission. However, in accordance with previous findings [1,39,40], we opted to measure FC (cut-off 250 µg/g) as a widely recognized biomarker of endoscopic remission.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the assessment of VDZ trough levels could be interesting in order to evaluate the correlation between serum cytokines and VDZ pharmacokinetics, although this evaluation is not widely performed in real-life practice. Lastly, an endoscopic assessment at twelve months would improve the significance of the results, although faecal calprotectin < 250 mg/kg is currently well recognized as a marker of endoscopic remission [28,30]. However, performing colonoscopies would allow to collect biopsies, in order to evaluate even histological healing and tissue cytokine levels, which could be another important weakness of our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, data regarding its use as a prospective biomarker in VDZ-treated patients are conflicting, since a post-hoc analysis of GEMINI-I trial showed that faecal calprotectin levels after the induction of VDZ therapy are not able to predict endoscopic response [27]. Conversely, faecal calprotectin showed in several studies in IBD setting a reliable correlation with endoscopic activity [28][29][30].…”
Section: Discussionmentioning
confidence: 99%